Efficacy of Penicillin-Streptomycin Brands against Staphylococcus aureus: Concordance between Veterinary Clinicians' Perception and the Realities - Takele Beyene Tufa; Asegid Guta; Tafese B. Tufa; Dereje Nigussie; Ashenafi Feyisa Beyi; Fanta D. Gutema; Fikru Regassa (MDPI AG, 2023)
Antibiotics must be safe and effective for use in both human and veterinary medicine. However, information about the efficacy of different brands of antibiotics commonly used in veterinary practices is lacking in Ethiopia. In this study, we determined the efficacy of three brands of penicillin-streptomycin (Pen&strep, Penstrep, and Pro&strep) by performing antimicrobial susceptibility testing against Staphylococcus aureus isolated from cow milk from dairy farms in the towns of Sebata and Bishoftu, Central Ethiopia. We also assessed the knowledge, attitudes, and practices (KAP) of veterinarians regarding the quality and use of brand antibiotics and the antibiotic utilization practices of dairy farm personnel using a structured questionnaire. Of 43 S. aureus isolated and tested, 33 (77%), 10 (23%), and 1 (2%) were susceptible to brands A, B, and C, respectively. According to the respondents, all of them reported that penstrep is the most prescribed antibiotic in dairy farms (100%), followed by oxytetracycline (78%) and sulfa drugs (52%). All veterinarians perceived that antibiotics imported from Western countries have a higher efficacy than those from Eastern countries, and they preferred brand A to the other brands, witnessing its better clinical outcome. The majority (87%) and a little more than half (53%) of the respondents perceived the overuse of antibiotics in veterinary clinics and dairy farms, respectively. Our study revealed the better efficacy of brand A against S. aureus compared to the other brands. Interestingly, the veterinarians' perception of and preference toward the use of brand antibiotics agreed with the findings of our antibacterial susceptibility testing. The prudent use of brand A is critically important for sustaining effective treatment, avoiding the risk of antimicrobial resistance, and helping to address animal welfare issues.